Le Corbusier’s Modern Museum Prototype: The Transformation of Unlimited Growth Museums - Chih-Ming Shih; Kuang-Hsu Huang (International Journal of Architectural Engineering Technology, 2014)
This paper analyzes how Le Corbusier constructed the prototype of the modern museum according to the concept of Unlimited Growth, and how he interpreted and implemented the prototype in three museums. Through analyzing and comparing the development of the concept of Unlimited Growth and its implementation across three aspects of design, namely modules, space arrangements, and natural lighting, we noticed that Le Corbusier did not limit his design thinking to mere prototypes; instead, through the implementation process, he redefined the core design of the modern museum by transferring the focus from Unlimited Growth to lighting design, which would later become one of the key design issues of contemporary museum design.